Utility of Follow-up Dopamine Transporter SPECT With 123I-FP-CIT in the Diagnostic Workup of Patients With Clinically Uncertain Parkinsonian Syndrome. (August 2017) - Apostolova, Ivayla; Taleb, Daulat S.; Lipp, Axel; Galazky, Imke; Kupitz, Dennis; Lange, Catharina; Makowski, Marcus R.; Brenner, Winfried; Amthauer, Holger; Plotkin, Michail; Buchert, Ralph
Abstract : Purpose: Dopamine transporter SPECT with 123 I-FP-CIT is registered for detection (or exclusion) of nigrostriatal degeneration to support the etiologic classification of parkinsonian syndromes. In case of uncertainty in the interpretation of SPECT findings or unexpected clinical course, follow-up SPECT might be useful. However, the utility of follow-up FP-CIT SPECT has not yet been clarified. Methods: One hundred forty-one patients (65.1 ± 10.4 years) from 3 sites with follow-up FP-CIT SPECT 22.4 ± 13.7 months after baseline SPECT were included. Retrospective visual interpretation of FP-CIT SPECT scans was performed by 2 experienced readers according to the following 7-point score: "normal, " some minor degree of uncertainty due to "mild asymmetry" or mild to moderate "uniform reduction, " "Parkinson disease (PD) reduction type 1/2/3, " and "atypical reduction." Results: Normal FP-CIT SPECT or PD characteristic reduction was confirmed by follow-up SPECT in all cases (n = 58). Among patients with some minor degree of uncertainty at baseline (n = 65), the majority (72%) did now show abnormalities in follow-up SPECT, but 20% showed clear progression suggesting nigrostriatal degeneration. The latter was very rare at age younger than 60 years. The final categorization as normal or neurodegenerative was not affected by the time delay between baseline and follow-up SPECT. Conclusions: Follow-up FP-CIT SPECT cannot be generally recommended in case of completely normal baseline SPECT or PD characteristic reduction. It also cannot be recommended in patients younger than 60 years, even in case of some minor degree of uncertainty in the baseline SPECT. There is no evidence to delay follow-up FP-CIT SPECT longer than 12 months.